Laminate and method for producing same

By using a laminated body with a specific structure in the battery case, combining thermoplastic resin, flame retardant and fibers, the problems of poor residual properties, dispersion and poor molding in the prior art are solved, and efficient flame shielding and safety are achieved.

CN119789954APending Publication Date: 2025-04-08MITSUBISHI CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380062284.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-13
Filing Date
2023-09-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has shortcomings in realizing the lightweighting and flame shielding of high-energy-density batteries. For example, additives in carbon fiber reinforced polypropylene resin compositions have problems with biological residues, poor dispersion of phosphorus-based flame retardant leads to a decrease in strength of the polypropylene-based resin, and problems with poor molding during molding.

Method used

A laminated body having a specific structure is adopted, including a resin layer and a support layer laminated on at least one surface of the resin layer. The resin layer is composed of a thermoplastic resin, a flame retardant and a fiber. The thickness of the resin layer is more than twice as thick as the thickness of the support layer, ensuring the flame shielding property of the laminated body.

Benefits of technology

A laminated body with excellent flame retardancy and especially excellent flame shielding is achieved, and the problems of poor residual property, poor dispersion and poor molding in the prior art are solved, and the safety of the battery case is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789954A_ABST
    Figure CN119789954A_ABST
Patent Text Reader

Abstract

Provided is a laminate having a resin layer and a support layer laminated on at least one surface of the resin layer, the resin layer being formed from a resin composition containing (A) a thermoplastic resin, (B) a flame retardant, and (C) fibers, the laminate having a thickness of 0.5 mm or more, and the thickness of the resin layer being twice or more of the thickness of the support layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate and a method for producing the same, and more particularly to a laminate having excellent flame retardancy and flame barrier properties. Background Art

[0002] In recent years, as part of environmental measures, research and development of electric vehicles and hybrid vehicles has been promoted, and the development and weight reduction of high-energy-density batteries with the goal of increasing driving range have been actively promoted. Such high-energy-density batteries may catch fire in accidents, and as a safety measure for passengers, their outer shell materials need to have high flame shielding properties, so most of them use metal materials such as iron and refractory materials together.

[0003] However, metal materials have the disadvantage of being heavy, and when used in combination with refractory materials, processability and increased cost due to increased number of parts become problems. Therefore, attempts have been made to make resins that have the potential to achieve both lightness and flame shielding properties.

[0004] On the other hand, in order to achieve a sustainable society, the suppression of carbon dioxide and recyclability are becoming more important. Most thermosetting materials have high flame retardancy and are usually made into composite materials, but thermoplastic resin raw materials are advantageous in terms of recyclability.

[0005] In addition, China has published the safety standard GB 38031-2020 "Safety requirements for electric vehicle power batteries", which requires an obligation to issue a warning 5 minutes before the thermal runaway of the battery, but it is believed that this can also be achieved by the casing material that shields the flame for more than 5 minutes after the battery catches fire.

[0006] To address these technical problems, for example, Patent Document 1 proposes a material in which a brominated flame retardant or an antimony oxide compound is added to a carbon fiber reinforced polypropylene resin. However, the additives used in this case have a problem in terms of bioresidue.

[0007] On the other hand, as a technique for flame-retarding a polypropylene-based resin in consideration of biopersistence, Patent Document 2 proposes a flame-retardant polyolefin-based composition comprising a polyolefin-based resin and a (poly)phosphate compound.

[0008] Furthermore, Patent Document 3 proposes a flame-retardant resin composition comprising long glass fibers and a phosphate compound contained in a polypropylene resin.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2014-62189

[0012] Patent Document 2: Japanese Patent Application Publication No. 2013-119575

[0013] Patent Document 3: Japanese Patent Application Publication No. 2011-88970 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] As described above, the prior art has many deficiencies in the resinization that has the possibility of achieving both lightweight and flame shielding properties for batteries with high energy density. Specifically, in the carbon fiber reinforced polypropylene resin composition disclosed in Patent Document 1, the additives used have the problem of bioresidue, and in terms of the carbon fiber length shown in the patent document, there is a problem that sufficient strength and rigidity of the molded body cannot be obtained.

[0016] In addition, the phosphorus flame retardant of the resin composition disclosed in Patent Document 2 has poor dispersibility. Although flame retardancy is obtained by adding a large amount of phosphorus flame retardant, there is a problem of greatly reducing the strength of the polypropylene resin. In addition, when a large amount of flame retardant is contained in the molded body, there is a problem of poor molding (unfilled molding) during molding.

[0017] Furthermore, the flame-retardant resin composition disclosed in Patent Document 3 needs to contain a large amount of phosphorus-based flame retardant, similarly to Patent Document 2, and has the problem that the mechanical properties of the molded body and the fluidity during molding cannot be maintained.

[0018] As described above, the flame-retardant resin compositions disclosed in Patent Documents 2 and 3 are insufficient in flame retardancy, particularly flame shielding properties, when it is necessary to simultaneously ensure mechanical properties of a molded product and fluidity during molding.

[0019] The present invention has been made to solve the above-mentioned problems, and a technical object thereof is to provide a laminate having excellent flame retardancy, particularly excellent flame barrier properties.

[0020] Technical Solution

[0021] The present inventors have conducted intensive research to solve the above technical problems and have found that the above technical problems can be solved by a laminate comprising: a resin layer having a specific structure and a support layer laminated on at least one surface of the resin layer, wherein the laminate has a specific thickness and the thickness of the resin layer is determined to be within a certain range relative to the thickness of the support layer. The present invention has been completed based on these findings. That is, the present invention provides the following [1] to

[19] .

[0022] [1] A laminate comprising a resin layer and a support layer laminated on at least one surface of the resin layer, wherein the resin layer is formed from a resin composition comprising (A) a thermoplastic resin, (B) a flame retardant, and (C) fibers, the thickness of the laminate being greater than 0.5 mm, and the thickness of the resin layer being greater than twice the thickness of the support layer.

[0023] [2] The laminate according to [1] above, wherein the support layer is a fiber layer formed of fibers (X).

[0024] [3] The laminate according to [2] above, wherein the fiber layer is a nonwoven fabric layer formed of a nonwoven fabric, a woven fabric layer formed of a woven fabric, or a knitted fabric layer formed of a knitted fabric.

[0025] [4] The laminate according to [2] or [3] above, wherein the average fiber length of the fibers (X) constituting the fiber layer is 5 mm to 100 mm.

[0026] [5] The laminate according to any one of [1] to [4] above, wherein the average fiber length of the fibers is 0.05 mm to 100 mm.

[0027] [6] The laminate according to any one of [1] to [5] above, wherein the resin composition further contains (D) a dispersant.

[0028] [7] The laminate according to any one of [1] to [6] above, wherein the thickness of the resin layer is 0.5 mm to 50 mm.

[0029] [8] The laminate according to any one of [1] to [7] above, wherein the flame retardant (B) contains a phosphorus-based flame retardant.

[0030] [9] The laminate according to any one of [1] to [8] above, wherein the flame retardant (B) comprises an intumescent flame retardant.

[0031]

[10] The laminate according to any one of [2] to [9] above, wherein the fibers (X) constituting the fiber layer include inorganic fibers.

[0032]

[11] The laminate according to

[10] above, wherein the inorganic fibers constituting the fiber layer include at least one selected from glass fibers, ceramic fibers, metal fibers, and metal oxide fibers.

[0033]

[12] The laminate according to any one of [1] to

[11] above, wherein the (C) fibers include inorganic fibers.

[0034]

[13] The laminate according to

[12] above, wherein the inorganic fiber includes at least one selected from glass fiber, ceramic fiber, metal fiber and metal oxide fiber.

[0035]

[14] The laminate according to any one of [6] to

[13] above, wherein the (D) dispersant comprises a copolymer of an α-olefin and an unsaturated carboxylic acid.

[0036]

[15] The laminate according to any one of [1] to

[14] above, wherein the (A) thermoplastic resin comprises a polypropylene resin, and the content of the polypropylene resin in the resin composition is 15% by mass to 80% by mass.

[0037]

[16] The laminate according to any one of [1] to

[15] above, wherein the content of the flame retardant (B) in the resin composition is 1% by mass to 40% by mass.

[0038]

[17] The laminate according to any one of [6] to

[16] above, wherein the content of the (D) dispersant is 0.1 to 25 parts by mass based on 100 parts by mass of the (B) flame retardant.

[0039]

[18] A method for manufacturing a laminate, which is a method for manufacturing a laminate as described in any one of [1] to

[17] above, comprising a step of impregnating a support with a resin composition to form a support layer laminated on at least one surface of a resin layer, wherein the thickness of the support before impregnation with the resin composition is 0.01 mm to 30 mm.

[0040]

[19] The method for producing a laminate according to

[18] above, wherein the compression rate of the support body defined as the ratio of the thickness of the support layer in the laminate body to the thickness of the support body before impregnation with the resin composition is 15% to 75%.

[0041] Effects of the Invention

[0042] According to the present invention, a laminate having excellent flame retardancy, particularly excellent flame barrier properties, can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a schematic diagram showing one embodiment of the laminated body of the present invention.

[0044] Figure 2 It is a schematic diagram showing the positional relationship between the laminated body of the present invention and the flame.

[0045] Figure 3 This is a schematic diagram showing another embodiment of the laminated body of the present invention.

[0046] Figure 4This is a schematic diagram showing still another embodiment of the laminated body of the present invention.

[0047] Figure 5 This is a schematic diagram showing an example of a method for producing the laminated body of the present invention.

[0048] Figure 6 This is a conceptual diagram showing a method for measuring the flexural modulus and flexural strength of a laminate in another embodiment of the present invention.

[0049] Figure 7 This is a conceptual diagram showing the structure of a battery in another embodiment of the present invention.

[0050] Figure 8 It is a schematic diagram showing the outline of the contact flame evaluation in the example of the present invention.

[0051] Explanation of symbols

[0052] 10: Laminated body

[0053] 11: Support layer

[0054] 12: Resin layer

[0055] 13: Flame retardant

[0056] 14. Fiber

[0057] 15: Support layer

[0058] 16: Resin composition

[0059] 21: Moving model

[0060] 22: Fixed mold

[0061] 100: Battery

[0062] 110: Battery module

[0063] 120: Battery pack

[0064] 130: Battery housing

[0065] Hereinafter, an embodiment of the present invention will be described in detail. However, the following description is an example of the embodiment of the present invention, and the present invention is not limited to these contents at all.

[0066] [Laminated body]

[0067] like Figure 1 As shown in the schematic diagram of , a laminate 10 according to one embodiment of the present invention comprises a resin layer 12 and a support layer 11 laminated on at least one surface of the resin layer 12, and has a thickness of 0.5 mm or more. The resin layer 12 contains a flame retardant 13 and fibers 14 as described below.

[0068] The invention is characterized in that the thickness of the resin layer is at least 2 times the thickness of the support layer. When the thickness of the resin layer is at least 2 times the thickness of the support layer, sufficient flame shielding properties can be imparted to the laminate. From the above viewpoints, the thickness of the resin layer is preferably at least 2.5 times the thickness of the support layer, more preferably at least 5 times, further preferably at least 8 times, and particularly preferably at least 10 times.

[0069] On the other hand, there is no particular limitation on the upper limit of the thickness of the resin layer relative to the thickness of the support layer except that the thickness of the laminate is 0.5 mm or more, and it can be appropriately determined according to the application, but is usually preferably 50 times or less, more preferably 45 times or less, further preferably 30 times or less, further preferably 20 times or less, and more preferably 15 times or less.

[0070] The thickness of the resin layer is not particularly limited as long as the above ratio is satisfied, but in order to obtain sufficient flame shielding properties, it is preferably 0.5 mm or more. On the other hand, the thickness of the resin layer has a preferred thickness depending on the application, but is generally preferably 50 mm or less. From the above viewpoints, the thickness of the resin layer is more preferably in the range of 1 mm to 25 mm, further preferably in the range of 1.3 mm to 15 mm, further preferably in the range of 1.5 mm to 10 mm, and particularly preferably in the range of 1.7 mm to 5 mm.

[0071] From the viewpoint of imparting a more excellent flame barrier property to the laminate, it is also preferred that the thickness of the resin layer is 70% or more relative to the total thickness of the resin layer and the support layer. From the same viewpoint, the thickness of the resin layer is more preferably 75% or more, further preferably 80% or more, and particularly preferably 85% or more relative to the total thickness of the resin layer and the support layer.

[0072] On the other hand, the upper limit of the thickness of the resin layer is not particularly limited and is appropriately determined depending on the intended use, but is usually preferably 98% or less, more preferably 95% or less.

[0073] The laminate of the present embodiment can be laminated with a resin layer and a supporting layer laminated on at least one surface of the resin layer, and the scheme of having an adhesive layer between the resin layer and the supporting layer is not excluded. From the viewpoint of improving flame shielding, the adhesion between the resin layer and the supporting layer is important, and it is preferred that the resin layer and the supporting layer are directly bonded without passing through other layers. From the same viewpoint, in the laminate, it is more preferred that at least a portion of the resin composition contained in the resin layer is melted and combined with the supporting layer to directly bond. In the laminate, it is particularly preferred that at least a portion of the resin composition contained in the resin layer is melted and impregnated in the above-mentioned supporting layer to combine and directly bond.

[0074] <Resin Layer>

[0075] The resin layer constituting the laminate of the present embodiment is formed of a resin composition comprising (A) a thermoplastic resin, (B) a flame retardant, and (C) fibers. Hereinafter, the (A) thermoplastic resin, (B) flame retardant, and (C) fibers constituting the resin composition will be described in detail.

[0076] <<(A) Thermoplastic resin>>

[0077] In the present embodiment, the thermoplastic resin contained in the resin composition constituting the resin layer is not particularly limited, and polyolefin resins, polycarbonate resins, polyester resins, acrylonitrile styrene resins, ABS resins, polyamide resins, modified polyphenylene ethers, polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, etc. can be listed. It should be noted that they can be used alone or in combination of two or more. For example, the thermoplastic resin (A) can be a composite resin of two or more thermoplastic resins among the above.

[0078] Among them, polyolefin resins are preferred, and polypropylene resins are particularly preferred, from the perspectives of physical properties, versatility, cost, and the like of the resins.

[0079] The polyolefin resin is not particularly limited, and the resins described below can be cited. The polyester resin is not particularly limited, and an example thereof is polybutylene terephthalate. The polyamide resin is not particularly limited, and an example thereof is nylon 66 and nylon 6.

[0080] The present embodiment is particularly useful when at least a polyolefin resin is included as the thermoplastic resin (A). It should be noted that in the present invention, "polyolefin resin" refers to a resin in which the proportion of olefin units or cycloolefin units is 90 mol% or more relative to 100 mol% of all structural units constituting the resin.

[0081] The proportion of the olefin unit or the cycloolefin unit relative to 100 mol % of all structural units constituting the polyolefin resin is preferably 95 mol % or more, particularly preferably 98 mol % or more.

[0082] Examples of the polyolefin resin include polyethylene, polypropylene, polybutene, poly(3-methyl-1-butene), poly(3-methyl-1-pentene), poly(4-methyl-1-pentene) and the like α-olefin polymers; α-olefin copolymers such as ethylene-propylene block or random copolymers, α-olefin-propylene block or random copolymers having 4 or more carbon atoms, ethylene-methyl methacrylate copolymers, ethylene-vinyl acetate copolymers and the like; cycloolefin polymers such as polycyclohexene and polycyclopentene, and the like.

[0083] Examples of polyethylene include low-density polyethylene, linear low-density polyethylene, and high-density polyethylene. Examples of polypropylene include isotactic polypropylene, syndiotactic polypropylene, hemi-isotactic polypropylene, and stereoblock polypropylene. Examples of α-olefins including butene, 3-methyl-1-butene, 3-methyl-1-pentene, and 4-methyl-1-pentene in α-olefin-propylene block or random copolymers having 4 or more carbon atoms.

[0084] Among them, in the laminate of the present embodiment, the (A) thermoplastic resin is particularly preferably a polypropylene-based resin. The polypropylene-based resin will be described in detail below.

[0085] It should be noted that the above-mentioned polyolefin resins may be used alone or in combination of two or more.

[0086] (Melt Flow Rate (MFR))

[0087] In the present embodiment, the melt flow rate (hereinafter sometimes referred to as MFR) of the (A) thermoplastic resin contained in the resin layer (230°C, 2.16 kg load) is preferably 5 g / 10 min to 500 g / 10 min. When the MFR is 5 g / 10 min or more, good fluidity is obtained when a molded body is made by, for example, injection molding, and the processability is good. On the other hand, when the MFR is 500 g / 10 min or less, the molded body has sufficient strength. From the above viewpoints, the MFR is preferably in the range of 10 g / 10 min to 300 g / 10 min, more preferably in the range of 20 g / 10 min to 200 g / 10 min, and further preferably in the range of 25 g / 10 min to 100 g / 10 min.

[0088] In addition, the MFR of the (A) thermoplastic resin can be adjusted by, for example, controlling the hydrogen concentration during polymerization, etc. In addition, MFR is a value measured in accordance with JIS K7210-1.

[0089] ((A) Content of thermoplastic resin)

[0090] In the present embodiment, the content of the thermoplastic resin (A) in the above-mentioned resin composition is not particularly limited, and is preferably 15% to 80% by mass. When the content of the thermoplastic resin is 15% by mass or more, the molding processability is particularly good, and the molding of the molded body becomes easy. On the other hand, when the content of the thermoplastic resin is 80% by mass or less, a sufficient amount of flame retardant, dispersant and inorganic fiber etc. can be contained to obtain good flame shielding properties. From the above viewpoints, the content of the thermoplastic resin in the resin composition is preferably 35% to 70% by mass, and more preferably 40% to 60% by mass. It should be noted that when the thermoplastic resin (A) is the above-mentioned preferred polypropylene resin, the preferred content is also the same.

[0091] <<(A-1) Polypropylene resin>>

[0092] In this embodiment, as the (A) thermoplastic resin constituting the above-mentioned resin composition, as described above, it is preferred to include a polypropylene resin. As the polypropylene resin, a propylene homopolymer or a propylene-α-olefin copolymer can be listed. Here, the propylene-α-olefin copolymer can be any copolymer of a random copolymer and a block copolymer.

[0093] (α-Olefins)

[0094] As the alpha-olefin constituting the above-mentioned copolymer, for example, ethylene, 1-butene, 2-methyl-1-propylene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, 1-octene, etc. can be listed. One of them can be used for copolymerization with propylene, in addition, two or more can also be used for copolymerization with propylene. Among them, from the viewpoint of improving the impact resistance of laminated body, preferably ethylene or 1-butene with large effect, most preferably ethylene.

[0095] (Propylene-ethylene random copolymer)

[0096] In the case of a random copolymer of propylene and ethylene, preferably 90% to 99.5% by mass, more preferably 92% to 99% by mass of propylene units, preferably 0.5% to 10% by mass, more preferably 1% to 8% by mass of ethylene units. When the ethylene units are above the above lower limit, sufficient impact strength of the laminate can be obtained, and in addition, when the ethylene units are below the above upper limit, sufficient rigidity can be maintained.

[0097] The contents of the propylene unit and the ethylene unit in the random copolymer of propylene and ethylene can be adjusted by controlling the composition ratio of propylene and ethylene during the polymerization of the random copolymer of propylene and ethylene.

[0098] The propylene content of the random copolymer of propylene and ethylene is a value measured using a cross-classifier, FT-IR or the like, and the measurement conditions and the like may be determined by the method described in, for example, JP-A-2008-189893.

[0099] <<<Modified polyolefin resin>>>

[0100] In this embodiment, the resin composition may further include a modified polyolefin resin in addition to the polypropylene resin. Specifically, the modified polyolefin resin includes an acid-modified polyolefin resin and a hydroxy-modified polyolefin resin, which may be used alone or in combination.

[0101] In addition, the types of the acid-modified polyolefin-based resin and the hydroxy-modified polyolefin-based resin used as the modified polyolefin-based resin are not particularly limited, and conventionally known resins may be used.

[0102] (Acid-modified polyolefin resin)

[0103] Examples of the acid-modified polyolefin resin include resins obtained by graft copolymerizing and chemically modifying polyolefins such as polyethylene, polypropylene, ethylene-α-olefin copolymers, ethylene-α-olefin-non-conjugated diene compound copolymers (EPDM, etc.), and ethylene-aromatic monovinyl compound-conjugated diene compound copolymer elastomers using unsaturated carboxylic acids such as maleic acid or maleic anhydride.

[0104] The graft copolymerization is carried out, for example, by reacting the polyolefin with an unsaturated carboxylic acid in an appropriate solvent using a free radical generator such as benzoyl peroxide. In addition, the unsaturated carboxylic acid or its derivative component can also be introduced into the polymer chain by random or block copolymerization with a monomer for polyolefin.

[0105] Examples of the unsaturated carboxylic acid used for modification include compounds having a polymerizable double bond in which a carboxyl group and, if necessary, a hydroxyl group, an amino group, or the like are introduced, such as maleic acid, fumaric acid, itaconic acid, acrylic acid, and methacrylic acid.

[0106] In addition, derivatives of unsaturated carboxylic acids include anhydrides, esters, amides, imides, metal salts, etc., and specific examples thereof include maleic anhydride, itaconic anhydride, methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, etc. Among them, maleic anhydride is preferred.

[0107] Preferred acid-modified polyolefin resins include resins modified by grafting maleic anhydride onto olefin polymers with ethylene and / or propylene as main polymer structural units, resins modified by copolymerizing maleic anhydride with olefins with ethylene and / or propylene as main components, etc. Specifically, combinations of polyethylene / maleic anhydride grafted ethylene-butene-1 copolymers, or combinations of polypropylene / maleic anhydride grafted polypropylene, etc. may be mentioned.

[0108] (Hydroxy-modified polyolefin resin)

[0109] The hydroxy-modified polyolefin-based resin is a modified polyolefin-based resin containing a hydroxy group. The hydroxy-modified polyolefin-based resin may have a hydroxy group at an appropriate position, such as at the terminal of the main chain or at a side chain.

[0110] Examples of the olefin resin constituting the hydroxy-modified polyolefin resin include homopolymers or copolymers of α-olefins such as ethylene, propylene, butene, 4-methylpentene-1, hexene, octene, nonene, decene, and dodecene, and copolymers of the α-olefins and copolymerizable monomers.

[0111] Preferred hydroxy-modified polyolefin resins include hydroxy-modified polyethylene resins such as low-density, medium-density or high-density polyethylene, linear low-density polyethylene, ultra-high molecular weight polyethylene, ethylene-(meth)acrylate copolymers, ethylene-vinyl acetate copolymers, and the like; and hydroxy-modified polypropylene resins such as polypropylene homopolymers such as isotactic polypropylene, random copolymers of propylene and α-olefins (such as ethylene, butene, hexene, etc.), propylene-α-olefin block copolymers, and the like.

[0112] <<(B) Flame retardant>>

[0113] In the present embodiment, the resin composition constituting the resin layer contains (B) a flame retardant. As (B) a flame retardant, there is no particular limitation, and for example, phosphorus flame retardants, bromine flame retardants, antimony flame retardants, etc. can be cited. Among them, from the viewpoint of improving flame shielding properties, phosphorus flame retardants are preferred. In addition, in the classification focusing on the mechanism of action of flame retardants, from the viewpoint of improving flame shielding properties, (B) flame retardants are preferably intumescent flame retardants.

[0114] (Phosphorus flame retardant)

[0115] The phosphorus-based flame retardant is a phosphorus compound, that is, a compound containing a phosphorus atom in the molecule. The phosphorus-based flame retardant forms char (carbonized film) when the resin composition is burned, thereby exhibiting a flame retardant effect.

[0116] The phosphorus-based flame retardant may be a known substance, for example, (poly)phosphate, (poly)phosphate ester, etc. Here, "(poly)phosphate" means a phosphate or a polyphosphate, and "(poly)phosphate ester" means a phosphate ester or a polyphosphate ester.

[0117] In addition, the phosphorus-based flame retardant is preferably solid at 80°C.

[0118] As the phosphorus-based flame retardant, (poly)phosphate is preferred from the viewpoint of flame retardancy.

[0119] Examples of the (poly)phosphate include ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, piperazine orthophosphate, melamine pyrophosphate, piperazine pyrophosphate, melamine orthophosphate, calcium phosphate, and magnesium phosphate.

[0120] In addition, in the above examples, compounds obtained by replacing melamine or piperazine with other nitrogen compounds may also be used. Examples of other nitrogen compounds include N,N,N',N'-tetramethyldiaminomethane, ethylenediamine, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, 1,2-propylenediamine, 1,3-propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, and the like. diamine, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, trans-2,5-dimethylpiperazine, 1,4-bis(2-aminoethyl)piperazine, 1,4-bis(3-aminopropyl)piperazine, acetoguanamine, benzoguanamine, acrylguanamine, 2,4-diamino-6-nonyl-1,3,5-triazine, 2,4-diamino-6-hydroxy-1,3,5-triazine, 2- Amino-4,6-dihydroxy-1,3,5-triazine, 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-ethoxy-1,3,5-triazine, 2,4-diamino-6-propoxy-1,3,5-triazine, 2,4-diamino-6-isopropoxy-1,3,5-triazine, 2,4-diamino-6-mercapto-1,3,5-triazine, 2-amino-4,6-dimercapto-1,3, 5-triazine, ammeline, benzoguanamine, acetoguanamine, phthalodiguanamine, cyanuric acid melamine, butylene biguanamine, norbornene biguanamine, methylene biguanamine, ethylene dimelamine, trimethylene bis melamine, tetramethylene bis melamine, hexamethylene bis melamine, 1,3-hexamethylene bis melamine, etc. These (poly) phosphates may be used alone or in combination of two or more.

[0121] As the phosphorus-based flame retardant, among the above, the salt of (poly)phosphoric acid and a nitrogen compound (hereinafter also referred to as "compound (B1)") is preferred. Compound (B1) is an intumescent flame retardant. An intumescent flame retardant is a flame retardant that inhibits the combustion of a material by forming a surface intumescent layer, which prevents radiant heat, combustion gas or smoke from the combustion source from diffusing to the outside. By forming a surface intumescent layer, the diffusion and heat transfer of decomposition products are inhibited, and excellent flame retardancy is exhibited.

[0122] As the nitrogen compound in compound (B1), ammonia, melamine, piperazine, the above-mentioned other nitrogen compounds, etc. can be listed. Specifically, ammonium salts and amine salts of (poly)phosphoric acid such as ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, ammonium pyrophosphate, melamine pyrophosphate, piperazine pyrophosphate can be listed. In addition, zinc oxide can also be contained as a flame retardant auxiliary. In this case, the flame retardant performance is further improved, so it is preferred.

[0123] Examples of commercially available phosphorus-based flame retardants include ADK STAB FP-2100J, FP-2200, and FP-2500S (manufactured by ADEKA Corporation).

[0124] (Brominated flame retardants)

[0125] Examples of the brominated flame retardant include decabromodiphenyl ether, tetrabromobisphenol A, tetrabromobisphenol S, 1,2-bis(2',3',4',5',6'-pentabromophenyl)ethane, 1,2-bis(2,4,6-tribromophenoxy)ethane, 2,4,6-tris(2,4,6-tribromophenoxy)-1,3,5-triazine, 2,6-dibromophenol, 2,4-dibromophenol, brominated polystyrene, ethylenebistetrabromophthalimide, hexabromocyclododecane, hexabromobenzene, pentabromobenzyl acrylate, 2,2-bis[4'(2",3"-dibromopropoxy)-3',5'-dibromophenyl]-propane, bis[3,5-dibromo-4-(2,3-dibromopropoxy)phenyl]sulfone, and tris(2,3-dibromopropyl)isocyanurate.

[0126] (Antimony flame retardant)

[0127] Examples of the antimony-based flame retardant include antimony trioxide, antimony tetroxide, antimony pentoxide, sodium pyroantimonate, antimony trichloride, antimony trisulfide, antimony oxychloride, antimony dichloride perchloropentane, and potassium antimonate. Antimony trioxide and antimony pentoxide are particularly preferred.

[0128] Among the flame retardants, phosphorus-based flame retardants are preferred from the perspective of no bioresidue and excellent flame retardancy, and halogen-free flame retardants are preferred from the perspective of environmental protection. In addition, intumescent flame retardants are preferred from the perspective of improving the flame shielding properties of the obtained laminate.

[0129] In addition, the above flame retardants may be used alone or in combination of two or more.

[0130] ((B) Content of flame retardant)

[0131] In the present embodiment, the content of the flame retardant in the resin composition is not particularly limited, and is preferably in the range of 1% by mass to 40% by mass. When the content of the flame retardant is 1% by mass or more, good flame retardancy can be imparted to the molded product, and good flame shielding properties can be obtained. On the other hand, when the flame retardant is 40% by mass or less, the thermoplastic resin can be contained with a sufficient content ratio, so the molding processability becomes better. From the above viewpoints, the content of the flame retardant in the resin composition in the present embodiment is more preferably in the range of 1% by mass to 35% by mass, further preferably in the range of 3% by mass to 30% by mass, and particularly preferably in the range of 5% by mass to 25% by mass.

[0132] <<(C) Fiber>>

[0133] In the present embodiment, the resin composition constituting the resin layer contains (C) fibers. As (C) fibers, organic fibers or inorganic fibers may be used, but from the perspective of heat resistance, inorganic fibers are preferred, such as glass fibers, rock wool, basalt fibers, alumina fibers, silica alumina fibers, potassium titanate fibers, calcium silicate (wollastonite) fibers, alkaline earth silicate fibers (biosolubility), ceramic fibers such as silica fibers or metal oxide fibers, carbon fibers, stainless steel fibers, tungsten fibers, and the like. These inorganic fibers may be used alone or in combination of two or more.

[0134] Among these inorganic fibers, at least one selected from the group consisting of glass fibers, ceramic fibers such as alumina fibers, metal oxide fibers, and carbon fibers is preferred in terms of improving heat resistance and flame shielding properties.

[0135] As the above-mentioned (C) fiber, the average fiber diameter is preferably 3μm to 25μm. In addition, the average fiber length is preferably in the range of 0.05mm to 100mm, more preferably in the range of 0.5mm to 50mm, further preferably in the range of 1mm to 25mm, and particularly preferably in the range of 2mm to 15mm. When the average fiber length is within the above range, the laminate having a resin layer containing a resin composition has more excellent mechanical strength (bending strength, etc.) and excellent heat resistance. Although not subject to specific theoretical constraints, it is believed that when the average fiber length is within the above range, there is a tendency for the above-mentioned fiber (C) to be oriented in the resin layer, so that the above-mentioned advantages can be obtained. If within the above range, there is a tendency that the longer the average fiber length, the more excellent the mechanical strength and heat resistance.

[0136] When a plurality of types of fibers are present, it is sufficient that the average fiber diameter and the average fiber length of at least one type of fiber are within the above ranges.

[0137] As for the (C) fiber contained in the resin composition, the average fiber length sometimes changes according to the manufacturing method of the laminate. For example, when using injection molding described later, since the resin composition is heated and melted, there is a tendency for the fiber to be damaged and the average fiber length to be shortened. The above-mentioned average fiber length refers to the average fiber length in the resin composition, which is the fiber length before applying the thermal history. Therefore, the average fiber length of the fibers in the laminate manufactured by methods such as injection molding is preferably in the range of 0.05mm to 50mm, more preferably in the range of 0.25mm to 25mm, further preferably in the range of 0.5mm to 15mm, and particularly preferably in the range of 1mm to 10mm.

[0138] On the other hand, when the laminate is produced by a lamination method, the average fiber length of the (C) fibers in the resin composition does not change from the average fiber length of the (C) fibers in the laminate.

[0139] It should be noted that the fiber diameter can be measured using an optical microscope, etc., and the average fiber diameter can be obtained by, for example, randomly measuring the fiber diameters of 10 fibers and calculating the average value. In addition, the fiber length can be measured using a ruler, a vernier caliper, etc., as needed, from an image magnified using a microscope, etc., and the average fiber length can be obtained by, for example, randomly measuring the fiber lengths of 10 fibers and calculating the average value.

[0140] ((C) Fiber content)

[0141] In the present embodiment, the content of the fiber in the resin composition is not particularly limited, and is preferably in the range of 3% to 60% by mass. When the content of the fiber is more than 3% by mass, the strength, rigidity and impact resistance of the laminate can be ensured. On the other hand, when the content of the fiber is less than 60% by mass, it is easy to manufacture and process the laminate. In addition, by making the content of the fiber less than 60% by mass, the specific gravity becomes small, and there is an advantage of a large lightweight effect as a metal substitute.

[0142] From the above viewpoints, the content of the fiber in the resin composition in the present embodiment is more preferably 10% by mass to 50% by mass, further preferably 20% by mass to 45% by mass, and further preferably 25% by mass to 40% by mass.

[0143] (Fiberglass)

[0144] One of the inorganic fibers (C) suitable for the laminate of this embodiment is glass fiber. The glass fiber may be, for example, long fibers having an average fiber length of 30 mm or longer, or fibers having a short average fiber length (chopped strands).

[0145] More specifically, as the average fiber length, it is preferably in the range of 0.05mm to 100mm. When the average fiber length is within the above range, the strength and impact resistance of the laminate are good. From the above viewpoints, it is more preferably in the range of 0.5mm to 50mm, further preferably in the range of 1mm to 25mm, and particularly preferably in the range of 2mm to 15mm. In the case of glass fibers as (C) fibers in a laminate manufactured by a method such as injection molding, the average fiber length is preferably in the range of 0.05mm to 50mm, more preferably in the range of 0.25mm to 25mm, further preferably in the range of 0.5mm to 15mm, and particularly preferably in the range of 1mm to 10mm.

[0146] It should be noted that the upper limit of the average fiber length of the glass fiber is not particularly limited. For example, when using particles made by pultrusion using glass fibers, the length of the particles is the fiber length of the glass fibers, so the maximum is about 20 mm. In addition, in a swirl mat system using long glass fibers, since the length of the glass fibers in the roving used in the manufacturing becomes the maximum fiber length, it also becomes about 17000 m (17 km), but when cutting according to the size of the laminate, the length after cutting is the maximum fiber length.

[0147] The average fiber diameter of the glass fiber is preferably in the range of 9 μm to 25 μm. When the average fiber diameter is 9 μm or more, the rigidity and impact resistance of the laminate are sufficient, and on the other hand, when the average fiber diameter is 25 μm or less, the strength of the laminate is good. From the above viewpoints, the average fiber diameter of the glass fiber is more preferably in the range of 10 μm to 15 μm.

[0148] It should be noted that the average fiber diameter and average fiber length of the glass fibers can be measured by the above-mentioned methods.

[0149] The material of the glass fiber used in the present embodiment is not particularly limited, and may be any of alkali-free glass, low-alkali glass, and alkali-containing glass, and glass fibers of various compositions conventionally used as glass fibers may be used.

[0150] (Alumina Fiber)

[0151] As one of the fibers (C) suitable for the laminate of the present embodiment, alumina fibers can be cited. Alumina fibers are generally fibers formed of alumina and silica, and in the laminate of the present invention, the composition ratio (mass ratio) of alumina / silica of the alumina fibers is preferably in the range of 65 / 35 to 98 / 2, which is called a mullite composition or a high alumina composition, more preferably in the range of 70 / 30 to 95 / 5, and particularly preferably in the range of 70 / 30 to 74 / 26.

[0152] The average fiber diameter of the alumina fiber is preferably in the range of 3 μm to 25 μm, and preferably substantially free of fibers with a fiber diameter of 3 μm or less. Here, substantially free of fibers with a fiber diameter of 3 μm or less means that fibers with a fiber diameter of less than 3 μm account for less than 0.1% by mass of the total inorganic fiber mass. When the average fiber diameter is 3 μm or more, the amount of dust floating in the air is reduced. On the other hand, when the average fiber diameter is 25 μm or less, it is preferred in terms of the rigidity and impact resistance of the laminate.

[0153] The average fiber length of the alumina fiber is preferably in the range of 0.05 mm to 100 mm. When the average fiber length is within the above range, the strength and impact resistance of the laminate are good. From the above viewpoints, it is more preferably in the range of 0.5 mm to 50 mm, further preferably in the range of 1 mm to 25 mm, and particularly preferably in the range of 2 mm to 15 mm. In the case of the alumina fiber as the (C) fiber in the laminate manufactured by a method such as injection molding, the average fiber length is preferably in the range of 0.05 mm to 50 mm, more preferably in the range of 0.25 mm to 25 mm, further preferably in the range of 0.5 mm to 15 mm, and particularly preferably in the range of 1 mm to 10 mm.

[0154] (Carbon Fiber)

[0155] The preferred ranges of the average fiber diameter and average fiber length of carbon fibers are the same as those of glass fibers.

[0156] In addition, in order to impart electromagnetic wave shielding properties, carbon fibers may be contained.

[0157] <<(D) Dispersant>>

[0158] In the present embodiment, the resin composition constituting the resin layer preferably contains a (D) dispersant in addition to the above-mentioned (A) to (C) components. As the (D) dispersant, there is no particular limitation as long as the (B) flame retardant can be dispersed in the (A) thermoplastic resin, but from the perspective of compatibility with the (A) thermoplastic resin, a polymer dispersant can be preferably used. Preferably, a dispersant that can disperse the (B) flame retardant in the (A-1) polypropylene resin can be used. As the polymer dispersant, a polymer dispersant having a functional group is preferred. From the perspective of dispersion stability, a polymer dispersant having functional groups such as carboxyl, phosphoric acid, sulfonic acid, primary amino, secondary amino or tertiary amino, quaternary ammonium base, pyridine, pyrimidine, pyrazine and the like is preferred.

[0159] In this embodiment, a polymer dispersant having a carboxyl group is preferably used, and in particular, a copolymer of an α-olefin and an unsaturated carboxylic acid is preferably used, wherein the dispersant can improve the dispersibility of the phosphorus flame retardant and reduce the content of the flame retardant.

[0160] (Copolymer of α-olefin and unsaturated carboxylic acid)

[0161] In the present embodiment, the ratio of the α-olefin unit to the unsaturated carboxylic acid unit in the above-mentioned "copolymer of α-olefin and unsaturated carboxylic acid" (hereinafter referred to as "copolymer (D1)") is preferably 20 mol% to 80 mol% based on the total 100 mol%.

[0162] In the copolymer (D1), the ratio of the α-olefin unit to the total amount of the α-olefin unit and the unsaturated carboxylic acid unit is more preferably 30 mol% or more, and on the other hand, is more preferably 70 mol% or less. If the ratio of the α-olefin is above the above lower limit, the compatibility with the (A) thermoplastic resin such as the polyolefin resin is better, and if the ratio of the α-olefin is below the above upper limit, the compatibility with the (B) flame retardant is better.

[0163] In the copolymer (D1), the α-olefin is preferably an α-olefin having 5 or more carbon atoms, and more preferably an α-olefin having 10 or more and 80 or less carbon atoms. If the α-olefin has 5 or more carbon atoms, there is a tendency for the compatibility with the thermoplastic resin (A) to become better, and if the α-olefin has 80 or less carbon atoms, it is advantageous in terms of raw material cost. From the above viewpoints, the α-olefin has more preferably 12 or more and 70 or less carbon atoms, further preferably 15 or more and 65 or less carbon atoms, and particularly preferably 18 or more and 60 or less carbon atoms.

[0164] In the copolymer (D1), examples of unsaturated carboxylic acids include (meth)acrylic acid, maleic acid, methylmaleic acid, fumaric acid, methylfumaric acid, tetrahydrophthalic acid, itaconic acid, crotonic acid, isocrotonic acid, glutaconic acid, norbornane-5-ene-2,3-dicarboxylic acid, and esters, anhydrides, and imides of these unsaturated carboxylic acids. It should be noted that "(meth)acrylic acid" means acrylic acid or methacrylic acid.

[0165] Specific examples of esters, anhydrides or imides of unsaturated carboxylic acids include (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and glycidyl (meth)acrylate; dicarboxylic anhydrides such as maleic anhydride, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride; maleimide compounds such as maleimide, N-ethylmaleimide, and N-phenylmaleimide, etc. These may be used alone or in combination of two or more.

[0166] Among the above, esters and dicarboxylic anhydrides are preferred from the viewpoint of copolymerization reactivity. Among them, dicarboxylic anhydrides are preferred from the viewpoint of compatibility with phosphorus-based flame retardants suitable as flame retardants, and maleic anhydride is particularly preferred.

[0167] The weight average molecular weight of the copolymer (D1) is preferably 2000 or more, more preferably 3000 or more, and is preferably 50000 or less, more preferably 30000 or less. When the weight average molecular weight of the copolymer (D1) is within the above range, the dispersibility of the flame retardant (B) is more excellent.

[0168] The weight average molecular weight of the copolymer (D1) is a value calculated in terms of standard polystyrene obtained by dissolving the copolymer (D1) in tetrahydrofuran (THF) and measuring the result by gel permeation chromatography.

[0169] Examples of commercially available products of the copolymer (D1) include Licolub CE2 (manufactured by Clariant Japan Co., Ltd.) and DIACANNA 30M (manufactured by Mitsubishi Chemical Corporation).

[0170] In the present embodiment, the content of the (D) dispersant in the resin composition is preferably in the range of 0.1 to 25 parts by mass, more preferably in the range of 1 to 10 parts by mass, and even more preferably in the range of 2 to 5 parts by mass, based on 100 parts by mass of the (B) flame retardant.

[0171] When the content of the dispersant (D) is at least the above lower limit, the flame retardant (B) is sufficiently dispersed and good flame barrier properties are easily obtained. On the other hand, when the content of the dispersant (D) is at most the above upper limit, the mechanical properties of the laminate can be maintained.

[0172] The ratio of (D) dispersant to a total of 100 parts by mass of (A) thermoplastic resin and (B) flame retardant is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and further preferably 0.1 parts by mass or more. On the other hand, it is preferably 10 parts by mass or less, more preferably 5.0 parts by mass or less, further preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and further preferably 1.0 parts by mass or less. If the ratio of (D) dispersant is above the above lower limit, (B) flame retardant is more well dispersed, and the flame shielding property, physical properties, and appearance of the laminate are better. If the ratio of (D) dispersant is below the above upper limit, the influence of (D) dispersant on the flame shielding property of the laminate can be further suppressed.

[0173] For (C) fiber, the ratio of (D) dispersant to 100 parts by mass of (C) fiber is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, further preferably 0.1 parts by mass or more, further preferably 0.5 parts by mass or more, and particularly preferably 1.0 parts by mass or more. On the other hand, it is preferably 10 parts by mass or less, more preferably 5.0 parts by mass or less, and further preferably 2.0 parts by mass or less. If the ratio of (D) dispersant is above the above lower limit, the flame shielding property, physical properties and appearance of the obtained molded body of the obtained laminate are better. If the ratio of (D) dispersant is below the above upper limit, the influence of (D) dispersant on the flame shielding property of the laminate can be further suppressed.

[0174] <<Optional Added Ingredients>>

[0175] In the present embodiment, in addition to the above-mentioned components, the resin composition may contain any additional components for the purpose of further improving the effects of the invention or imparting other effects, within a range that does not significantly impair the effects of the invention.

[0176] Specifically, colorants, light stabilizers, ultraviolet absorbers, nucleating agents such as sorbitol, antioxidants, antistatic agents, neutralizing agents such as inorganic compounds, antibacterial / antifungal agents such as thiazole, flame retardants / flame retardant aids such as halogen compounds or lignin phenol, plasticizers, dispersants such as organic metal salts, lubricants such as fatty acid amides, metal deactivators such as nitrogen compounds, thermoplastic resins such as polyolefin resins other than the above-mentioned polypropylene resins, polyamide resins, polyester resins, and elastomers (rubber components) such as olefin elastomers and styrene elastomers, etc. can be listed.

[0177] These optional additional components may be used in combination of two or more.

[0178] Colorants such as inorganic and organic pigments are effective in imparting or improving the colored appearance, beauty, feel, commercial value, weather resistance, durability, etc. of the resin composition and a laminate having a resin layer formed from the resin composition.

[0179] As specific examples, inorganic pigments include carbon black such as furnace carbon and ketjen carbon; titanium oxide; iron oxide (iron oxide red, etc.); chromic acid (chrome yellow, etc.); molybdic acid; selenium sulfide; ferrocyanide, etc., and organic pigments include azo pigments such as poorly soluble azo lakes, soluble azo lakes, insoluble azo chelates; condensed azo chelates; other azo chelates; phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; threonine pigments such as anthraquinone, perinone, perylene, and thioindigo; dye lakes; quinacridone series; dioxazine series; isoindolinone series, etc. In addition, in order to form a metallic style or a pearlescent style, aluminum flakes and pearlescent pigments may be contained. In addition, dyes may also be contained.

[0180] Light stabilizers and ultraviolet absorbers, such as hindered amine compounds, benzotriazole series, benzophenone series, salicylate series, etc., are effective in imparting and improving the weather resistance and durability of the above-mentioned resin composition and a laminate having a resin layer formed from the resin composition, and are effective in further improving the weather resistance and discoloration.

[0181] As specific examples, hindered amine compounds include condensates of dimethyl succinate and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine; poly[[6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidyl)imino]]; tetrakis(2,2,6,6-tetramethyl-4-piperidyl)1,2,3,4-butanetetracarboxylate; tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)1,2,3,4-butanetetracarboxylate; di ... (1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate; bis-2,2,6,6-tetramethyl-4-piperidinyl sebacate, etc., as benzotriazole series, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole; 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, etc., as benzophenone series, 2-hydroxy-4-methoxybenzophenone; 2-hydroxy-4-n-octyloxybenzophenone, etc., as salicylate series, 4-tert-butylphenyl salicylate; 2,4-di-tert-butylphenyl 3',5'-di-tert-butyl-4'-hydroxybenzoate, etc. can be listed.

[0182] Here, the method of using the above-mentioned light stabilizer and ultraviolet absorber in combination is preferred because it has a great effect of improving weather resistance, durability, weather resistance and discoloration resistance.

[0183] As the antioxidant, for example, phenolic, phosphorus or sulfur antioxidants are effective for imparting or improving the heat resistance stability, processing stability, heat aging resistance and the like of the polypropylene resin composition and its molded article.

[0184] In addition, as the antistatic agent, for example, a nonionic antistatic agent, a cationic antistatic agent or the like is effective for imparting or improving the antistatic property of the resin composition and a laminate having a resin layer formed of the resin composition.

[0185] As olefin-based elastomers, for example, there can be listed ethylene-α-olefin copolymer elastomers such as ethylene-propylene copolymer elastomer (EPR), ethylene-butene copolymer elastomer (EBR), ethylene-hexene copolymer elastomer (EHR), and ethylene-octene copolymer elastomer (EOR); ethylene-α-olefin-diene terpolymer elastomers such as ethylene-propylene-ethylidene norbornene copolymer, ethylene-propylene-butadiene copolymer, and ethylene-propylene-isoprene copolymer; and styrene-butadiene-styrene triblock copolymer elastomer (SBS).

[0186] Examples of the styrene-based elastomer include styrene-isoprene-styrene triblock copolymer elastomer (SIS), styrene-ethylene / butylene copolymer elastomer (SEB), styrene-ethylene / propylene copolymer elastomer (SEP), styrene-ethylene / butylene-styrene copolymer elastomer (SEBS), styrene-ethylene / butylene-ethylene copolymer elastomer (SEBC), hydrogenated styrene-butadiene elastomer (HSBR), styrene-ethylene / propylene-styrene copolymer elastomer (SEPS), styrene-ethylene / ethylene / propylene-styrene copolymer elastomer (SEEPS), styrene-butadiene / butylene-styrene copolymer elastomer (SBBS), partially hydrogenated styrene-isoprene-styrene copolymer elastomer, partially hydrogenated styrene-isoprene / butadiene-styrene copolymer elastomer and the like; and hydrogenated polymer-based elastomers such as ethylene-ethylene / butylene-ethylene copolymer elastomer (CEBC) and the like.

[0187] Among them, the use of ethylene-octene copolymer elastomer (EOR) and / or ethylene-butene copolymer elastomer (EBR) is preferred from the viewpoints of being able to easily impart appropriate flexibility to the laminate of the present embodiment and tending to have excellent impact resistance.

[0188] <<Method for producing resin composition>>

[0189] In the present embodiment, as a method for producing the resin composition, a conventionally known method can be used, and the resin composition can be produced by blending the above components, mixing, and melt-kneading.

[0190] Mixing is performed using a mixer such as a tumbler, a V-type mixer, or a ribbon mixer, and melt kneading and granulation are performed using a machine such as a single-screw extruder, a twin-screw extruder, a Banbury mixer, a roll mixer, a Brabender mixer (Brabender Plastograph), or a kneader.

[0191] <Supporting layer>

[0192] The laminated body of the present embodiment is obtained by laminating a support layer on at least one surface of the above-mentioned resin layer.

[0193] The supporting layer is integrated with the resin layer so that the laminate of the present invention exhibits flame retardancy and flame shielding properties. From the perspective of exerting these effects, it is preferably a fiber layer formed by fiber (X), among which a non-woven fabric layer formed by a non-woven fabric, a woven fabric layer formed by a woven fabric, or a woven fabric layer formed by a knitted fabric is preferred.

[0194] In particular, nonwoven fabrics are preferred in that a portion of the resin layer easily penetrates the surface of the support layer compared to woven fabrics and knitted fabrics, and the adhesiveness becomes higher. In addition, nonwoven fabrics are also preferred in that the orientation direction of the fibers is irregular, and therefore the mechanical strength does not have a directional dependence.

[0195] As the thickness of the supporting layer, as long as it is a range that can make the thickness of the laminated body be more than 0.5mm, there is no particular restriction, preferably more than 0.01mm. If it is more than 0.01mm, the adhesion with the resin layer is good, and the resin layer can be maintained even if the flame contacts the resin layer. Considering from the above viewpoints, the thickness of the supporting layer is more preferably more than 0.05mm, and further preferably more than 0.1mm.

[0196] On the other hand, the upper limit of the thickness of the support layer is preferably 5 mm or less, more preferably 2 mm or less, further preferably 1 mm or less, and particularly preferably 0.5 mm or less, from the perspective of being able to suppress the weight and cost of the molded body.

[0197] The size of the fibers (X) constituting the fiber layer is not limited within the range in which the effects of the present invention are exhibited, but the average fiber diameter (diameter) is preferably in the range of 3 μm to 25 μm, and the average fiber length is preferably in the range of 5 mm to 100 mm.

[0198] When the average fiber diameter is 3 μm or more, the fiber layer is easy to handle during the manufacturing process, and when the average fiber diameter is 25 μm or less, it is not easy to be damaged. In addition, when the average fiber length is 5 mm or more, flame shielding properties can be given to the laminate, and sufficient strength can be given. On the other hand, when the average fiber length is 100 mm or less, it is not easy to be damaged. The fiber length can be measured as needed by using a ruler, a vernier caliper, etc. by using an image magnified by a microscope, etc., and the average fiber length can be obtained by randomly measuring the fiber lengths of 10 fibers and calculating the average value.

[0199] The fiber (X) constituting the fiber layer is not particularly limited as long as the effects of the present invention are exhibited, and examples thereof include inorganic fibers such as glass fibers, carbon fibers, boron fibers, ceramic fibers, metal fibers, and metal oxide fibers; and organic fibers such as aramid fibers and aromatic polyester fibers. Among them, inorganic fibers are preferred from the perspective of obtaining excellent flame shielding properties, and among them, glass fibers, ceramic fibers, metal fibers, and metal oxide fibers are preferred, and glass fibers are particularly preferred.

[0200] As mentioned above, in the fiber, at least one of the group consisting of glass fiber and aramid fiber is preferably selected. As described below, when a laminate is used in a battery pack, it is desirable to have excellent flame shielding. In this case, safety when the flame is contacted from the resin layer side is required. The inventors found that both glass fiber and aramid fiber can withstand contact with flame from the resin layer side, but if glass fiber is selected, it can also withstand contact with flame from the supporting layer side constituting the laminate. Therefore, as the fiber (X) constituting the fiber layer, glass fiber is more preferred.

[0201] <<Non-woven fabric layer>>

[0202] The nonwoven fabric layer is formed of nonwoven fabric. As the fibers constituting the nonwoven fabric, there is no particular limitation as long as the effects of the present invention are exerted, and examples thereof include inorganic fibers such as glass fibers, carbon fibers, boron fibers, ceramic fibers, metal fibers, and metal oxide fibers; and organic fibers such as aramid fibers and aromatic polyester fibers. Among them, inorganic fibers are preferred from the perspective of obtaining excellent flame shielding properties, and among them, glass fibers, ceramic fibers, metal fibers, and metal oxide fibers are preferred, and glass fibers are particularly preferred.

[0203] (Glass fiber non-woven fabric)

[0204] As the form of glass fiber nonwoven fabric preferably used in the present invention, there can be listed mats and blankets made of short fiber glass wool, chopped strand mats made of continuous glass fibers, eddy flow (vortex) mats of continuous glass fibers, unidirectionally drawn mats, etc. Among them, when a glass fiber mat made by needle-punching eddy flow (vortex) mats of continuous glass fibers is used, the strength and impact resistance of the laminate are excellent, so it is preferred.

[0205] In addition, the glass fiber is the same as the glass fiber mentioned in (C) fiber.

[0206] As the ceramic fiber, preferably, it is a fiber mainly composed of silica and alumina, for example, in the range of silica:alumina=40:60 to 0:100. Specifically, silica-alumina fiber, mullite fiber, and alumina fiber can be used.

[0207] As the material of the metal fiber, preferably, the fiber mainly contains iron, copper, aluminum, nickel, tungsten, titanium, molybdenum, beryllium, platinum, etc. Furthermore, as an alloy component, in addition to the above metals, one or more of carbon, nitrogen, chromium, cobalt, gold, silver, etc. may be contained. In terms of excellent strength and corrosion resistance, the fiber mainly contains stainless steel, nickel or titanium is particularly preferred.

[0208] As the material of the metal oxide fiber, for example, alkaline earth metal oxides such as magnesium oxide and calcium oxide; metal oxides of Group IVB such as titanium oxide and zirconium oxide; oxides of Group IIIA elements such as aluminum oxide and indium oxide; oxides of Group IVA elements such as silicon dioxide, tin oxide and lead oxide; oxides of Group VA elements such as antimony oxide, etc. Among them, from the perspective of effectively obtaining a high level of heat resistance, fibers of oxides of Group IIIA to Group VA elements are preferred, fibers of oxides of Group IIIA elements are more preferred, and aluminum oxide fibers are particularly preferred.

[0209] The size of the fibers constituting the nonwoven fabric is not limited within the range in which the effects of the present invention are exhibited, but the average fiber diameter is preferably in the range of 3 μm to 25 μm, and the average fiber length is preferably in the range of 5 mm to 100 mm.

[0210] When the average fiber diameter is 3 μm or more, the nonwoven fabric is easy to handle during the manufacturing process, and when the average fiber diameter is 25 μm or less, it is not easy to be damaged. In addition, when the average fiber length is 5 mm or more, flame shielding properties can be given to the laminate, and sufficient strength can be given. On the other hand, when the average fiber length is 100 mm or less, it is not easy to be damaged. From the above viewpoints, the average fiber length is more preferably in the range of 10 mm to 50 mm, and more preferably in the range of 15 mm to 30 mm.

[0211] It should be noted that the average fiber length can be measured by the above-mentioned method.

[0212] The weight per unit area of ​​the nonwoven fabric (the amount of fibers per unit area) is preferably 10 g / m 2 ~500g / m 2 When the unit area weight is 10g / m 2 When the weight per unit area is 500 g / m 2 When the weight per unit area is less than 20 g / m, the adhesion with the resin layer is good, sufficient flame shielding of the laminate can be obtained, and the weight is not too large. From the above viewpoints, the weight per unit area is more preferably 20 g / m 2 ~300g / m 2 The range is more preferably 30g / m 2 ~150g / m 2 The range is particularly preferably 35g / m 2 ~100g / m 2 range.

[0213] Above 35g / m 2 ~100g / m 2The weight per unit area is preferably 35 g / m 2 ~75g / m 2 , more preferably 35g / m 2 ~70g / m 2 , more preferably 35g / m 2 ~45g / m 2 Although not being bound by a particular theory, it is considered that the lower the weight per unit area is, the easier it is for the resin composition containing the flame retardant to penetrate through the resin layer, resulting in better flame shielding properties as a whole.

[0214] As a method for producing the nonwoven fabric, a conventionally known method can be used, for example, a dry method, a wet method, a spunbond method, a meltblown method, an air-laid method, etc. In addition, as a method for bonding the fibers of the nonwoven fabric obtained by these production methods, a chemical bonding method, a thermal bonding method, a needle punching method, a water-entangled method, etc., a conventionally known method can be used.

[0215] <<Fabric Layer>>

[0216] The woven fabric layer is formed by woven fabric. As the fiber constituting the woven fabric, there is no particular limitation as long as the effect of the present invention is exerted, and the same fiber as the fiber exemplified in the above-mentioned nonwoven fabric layer can be used. It should be noted that, as with the nonwoven fabric layer, inorganic fibers are preferred, and glass fibers are particularly preferred.

[0217] The size (average fiber diameter, average fiber length) and basis weight of the fibers constituting the woven fabric are also the same as those described for the nonwoven fabric layer.

[0218] The weave of the woven fabric formed from the above fibers is not particularly limited, and may be any of plain weave, twill weave, satin weave, and the like.

[0219] << Braid layer>>

[0220] The woven fabric layer is formed by a woven fabric. As the fiber constituting the woven fabric, there is no particular limitation as long as the effect of the present invention is exerted, and the same fiber as the fiber exemplified in the above-mentioned nonwoven fabric layer can be used. It should be noted that, like the nonwoven fabric layer, inorganic fibers are preferred, and glass fibers are particularly preferred.

[0221] The size (average fiber diameter, average fiber length) and basis weight of the fibers constituting the woven fabric are also the same as those described for the nonwoven fabric layer.

[0222] The weave structure of the knitted fabric formed of the above-mentioned fibers is not particularly limited, and may be any of rib knitting, garter stitch, stockinette stitch, and the like.

[0223] <Method for producing laminate>

[0224] The manufacturing method of the laminate of the present embodiment is not particularly limited, and various known methods can be used. Specifically, a method of pre-forming a resin layer and a support layer and laminating them; a method of placing the support layer in a mold, injecting a resin composition for forming a resin layer, and performing injection molding, etc. can be cited.

[0225] As a method of laminating, for example, there is a method of preparing in advance a resin sheet for constituting the resin layer and a glass fiber nonwoven fabric sheet for constituting the support layer, laminating them, and heating and pressing them.

[0226] More specifically, it is a method of press-molding a resin sheet and a glass fiber nonwoven fabric sheet in a mold equipped with a heating device.

[0227] The heating temperature is preferably 170° C. to 300° C. When the heating temperature is 170° C. or higher, the resin layer and the support layer are sufficiently bonded, and the flame barrier properties of the laminate are improved. On the other hand, when the heating temperature is 300° C. or lower, the resin composition constituting the resin layer does not deteriorate.

[0228] The pressurization pressure is preferably 0.1 MPa to 1 MPa. When the pressurization pressure is 0.1 MPa or more, the resin layer and the support layer are sufficiently bonded, and the flame barrier property of the laminate is improved. On the other hand, by setting the pressurization pressure to 1 MPa or less, burrs are not generated on the resin layer.

[0229] When the resin layer and the support layer are bonded together, an adhesive layer may be disposed between the resin layer and the support layer. However, in the present invention, since the adhesion between the resin layer and the support layer is important, it is preferred that the resin layer and the support layer are directly bonded without intervening other layers.

[0230] The cooling temperature is not particularly limited as long as it is below the solidification point of the thermoplastic resin, but when the cooling temperature is 80° C. or below, the obtained molded body will not be deformed when taken out. From the above viewpoints, the cooling temperature is preferably room temperature to 80° C.

[0231] The laminate can also be produced by laminating the resin sheet and the glass fiber nonwoven fabric sheet by passing them between two pairs of rollers equipped with a heating device and applying heat and pressure. Laminating is preferred because it allows continuous production and thus has good productivity.

[0232] As a method for producing a laminate by injection molding, for example, Figure 5The method shown. That is, the glass nonwoven fabric that will become the support layer 15 is set in the movable mold 21, the movable mold 21 is embedded in the fixed mold 22, the resin composition 16 is injected into the mold cavity, and the resin composition 16 and the glass nonwoven fabric (support layer 15) are integrally molded. By this method, the laminated body 10 of the present invention in which the support layer 11 is laminated on one surface of the resin layer 12 can be obtained. When this injection molding method is used, the long fibers in the glass nonwoven fabric will not be broken and are maintained, so the flame shielding property of the laminated body of this embodiment can be further improved.

[0233] As a preferred example of the method for producing the laminated body according to the present embodiment, the following method can be mentioned.

[0234] That is, a method for manufacturing a laminated body, comprising the step of impregnating a support with a resin composition to form a support layer laminated on at least one surface of a resin layer. The method of impregnating the support with the resin composition is not particularly limited, and can be performed by the following methods: a method of performing press molding while heating a resin sheet and a support in a mold with a heating device; a method of pre-arranging a support in a mold for injection molding and injecting a resin, etc.

[0235] The thickness of the support before impregnation with the resin composition is preferably 0.01 mm to 30 mm. As described below, the thickness of the support used in the manufacture of the laminate is sometimes different from the thickness of the support layer in the manufactured laminate. This is because the support is compressed during the manufacture of the laminate. Therefore, when manufacturing the laminate, it is desirable to consider the compression of the support.

[0236] When the thickness of the support before impregnation with the resin composition is within the above range, the productivity of the laminate, the flame shielding properties of the obtained laminate, and the strength are excellent. From the above viewpoints, the thickness of the support is more preferably 0.05 mm to 15 mm, further preferably 0.5 mm to 5 mm, and particularly preferably 1 mm to 3 mm.

[0237] In the method for manufacturing a laminate, the support compression ratio, which is defined as the ratio of the thickness of the support layer in the laminate to the thickness of the support before impregnation with the resin composition, is preferably 15% to 75%. When the support compression ratio is within this range, the productivity of the laminate, the flame shielding properties of the obtained laminate, and the strength are excellent. From the above viewpoints, the support compression ratio is more preferably 20% to 60%, further preferably 25% to 50%, and particularly preferably 30% to 40%.

[0238] <Mechanism of flame shielding>

[0239] like Figure 2As shown in the schematic diagram of , the laminate 10 of the present embodiment holds the resin layer 12 by the support layer 11, so when the resin layer contacts the flame, the resin layer can be suppressed from melting and falling. Moreover, it is believed that the char formed by the flame retardant 13 contacting the flame is stably formed in the resin layer. At this time, by making the thickness of the resin layer within a specific range relative to the thickness of the support layer, the resin layer functions perfectly as a heat insulating layer when contacting the flame, and the support layer can be effectively protected from high heat. Therefore, due to the heat insulation effect of the char, the temperature of the support layer will not rise to the softening point, so the support layer can exist stably and maintain the holding effect of the resin layer. As a result, it is believed that the flame will not penetrate for a long time.

[0240] In particular, the laminate 10 of the present embodiment includes the fiber 14 in the resin layer 12, so it can be considered that the flame retardant 13 is uniformly dispersed. Moreover, since the flame retardant is uniformly dispersed in the resin between the fibers, the coke formed by the flame retardant contacting the flame is fixed in the gaps between the fibers. Furthermore, the size of the coke formed by expansion when contacting the flame is limited by the gaps between the fibers, thereby making the size of the formed coke uniform. It can be considered that by combining the fixing effect of the fiber on the coke and the uniformization of the size of the coke, a dense coke is formed, and the flame shielding property of the laminate is significantly improved.

[0241] In particular, it is considered that by controlling the content ratio of the dispersant to the flame retardant to be within a specific range, the flame retardant can be controlled to be uniformly present in the resin between the fibers, and the flame barrier properties of the laminate can be significantly improved.

[0242] <Other options for laminated bodies>

[0243] The laminate of the present invention comprises a resin layer and a support layer. The support layer may be located on one side of the resin layer. Figure 3 As shown, there are support layers 11 on both sides of the resin layer 12. In this embodiment, since the support layer 11 contacts the flame, the support layer 11 that contacts the flame no longer functions as a support layer, but since the other support layer 11 functions as a support layer, flame shielding properties are exerted through the same mechanism of action as described above.

[0244] In this embodiment, since the support layer 11 is provided on both surfaces of the resin layer 12, the laminated body does not warp, which is preferable.

[0245] Moreover, if Figure 4 As shown, the laminate 10 of the present invention may also be an embodiment in which two resin layers 12 are present so as to sandwich the support layer 11. In the case of this embodiment, the effect of the present invention is achieved regardless of which of the upper surface and the lower surface contacts the flame.

[0246] In another embodiment of the present invention (also described as a second embodiment), the laminate preferably satisfies at least one of the following conditions (a1) and (b1).

[0247] Condition (a1): The minimum value of the flexural modulus measured in accordance with JIS K7171 (ISO 178) is 1000 MPa or more;

[0248] Condition (b1): The minimum value of the flexural strength measured in accordance with JIS K7171 (ISO 178) is 10 MPa or more.

[0249] In the laminated body of the second embodiment, it is preferred that either the condition (a1) or the condition (b1) described above is satisfied, and it is more preferred that both the conditions (a1) and (b1) are satisfied.

[0250] When the laminate satisfies at least one of the above conditions (a1) and (b1), sufficient flame shielding properties can be given to the laminate. It should be noted that the minimum value of the bending modulus measured according to JIS K7171 (ISO 178) refers to the minimum value of the bending modulus measured in any direction parallel to the plane of the laminate. Usually, the numerical value of the bending modulus is different according to the direction in which the bending modulus is measured relative to the plane of the laminate. Typically, there are many cases where the numerical value of the bending modulus measured in the flow direction of the resin layer constituting the laminate is the largest, and there are many cases where the numerical value of the bending modulus measured in the direction orthogonal to the flow direction is the smallest. In addition, depending on the direction in which the laminate as a test piece is applied with force during measurement, the numerical value of the bending modulus is sometimes different. For example, there is a case where a force is applied to the resin layer side of the laminate and a case where a force is applied to the support layer side, but in this case, the minimum value of the bending modulus when a force is applied from any direction is taken as the minimum value of the bending modulus.

[0251] The bending strength is similar to the bending elastic modulus. The minimum value of the bending strength measured in any direction parallel to the plane of the laminate is taken as the minimum value of the bending strength.

[0252] The laminate in the second embodiment preferably satisfies the above-mentioned condition (a1). That is, the minimum value of the bending elastic modulus measured according to JIS K7171 (ISO 178) is preferably more than 1000MPa. In this case, the laminate can be given enough flame shielding properties. From the above viewpoint, the minimum value of the bending elastic modulus is more preferably more than 2000MPa, further preferably more than 2500MPa, and particularly preferably more than 3000MPa (condition (a2)).

[0253] With regard to the laminate in the second embodiment, from the viewpoint of improving the flame shielding property of the laminate, it is also preferred that the numerical value of the bending elastic modulus measured in the flow direction of the resin and the average value of the bending elastic modulus measured in the direction orthogonal to the flow direction be more than 3000MPa (condition (a3)). It is particularly preferred to satisfy the above-mentioned condition (a1) and satisfy the condition (a3). The average value of the bending elastic modulus in the flow direction and the bending elastic modulus in the direction orthogonal to the flow direction is more preferably more than 4000MPa, and further preferably more than 5000MPa. On the other hand, the upper limit is usually below 10GPa. It should be noted that the flow direction of the resin can be confirmed by observing the cross section of the laminate.

[0254] The laminate in the second embodiment also preferably satisfies the above-mentioned condition (b1). That is, the minimum value of the bending strength measured according to JIS K7171 (ISO178) is preferably more than 10MPa. In this case, sufficient flame shielding properties can be given to the laminate. From the above viewpoints, the minimum value of the bending elastic modulus is more preferably more than 20MPa, further preferably more than 2500MPa, and particularly preferably more than 30MPa (condition (b2)).

[0255] With regard to the laminate in the second embodiment, from the viewpoint of improving the flame shielding properties of the laminate, it is also preferred that the average value of the bending strength measured in the flow direction of the resin and the bending strength measured in the direction perpendicular to the flow direction is 30 MPa or more (condition (b3). It is particularly preferred that the above-mentioned condition (b1) and the condition (b3) are satisfied. The average value of the bending modulus in the flow direction and the bending modulus in the direction perpendicular to the flow direction is more preferably 50 MPa or more, and further preferably 80 MPa or more. On the other hand, the upper limit is usually 1000 MPa or less. It should be noted that the flow direction of the resin can be confirmed by observing the cross-section of the laminate as described above.

[0256] In the laminate of the second embodiment, from the viewpoint of improving the flame shielding property of the laminate, it is preferred that the ratio of the average value of the bending strength measured in the flow direction of the resin when a force is applied to one surface and the average value of the bending strength measured in the direction perpendicular to the flow direction to the average value of the bending strength measured in the flow direction of the resin when a force is applied to the surface opposite to the surface is 105% or more. The above ratio is more preferably 110% or more and usually 300% or less.

[0257] With regard to the laminate of the second embodiment, from the viewpoint of improving the flame shielding properties of the laminate, it is preferred that the average value of the bending strength measured in the flow direction of the resin and the bending strength measured in a direction perpendicular to the flow direction when a force is applied to the surface on the resin layer side is greater than the average value of the bending strength measured in the flow direction of the resin and the bending strength measured in a direction perpendicular to the flow direction when a force is applied to the surface on the supporting layer side.

[0258] In the laminate of the second embodiment, from the viewpoint of improving the flame shielding property of the laminate, it is preferred that the ratio of the average value of the bending modulus of elasticity measured in the flow direction of the resin and the bending strength measured in the direction perpendicular to the flow direction when a force is applied to one surface to the average value of the bending strength measured in the flow direction of the resin and the bending modulus of elasticity measured in the direction perpendicular to the flow direction when a force is applied to the surface on the opposite side of the surface exceeds 100%. The above ratio is more preferably 102% or more, further preferably 105% or more, and usually 300% or less.

[0259] With regard to the laminate of the second embodiment, from the viewpoint of improving the flame shielding properties of the laminate, it is preferred that the average value of the bending modulus measured in the flow direction of the resin and the average value of the bending modulus measured in the direction perpendicular to the flow direction when a force is applied to the surface on the resin layer side is greater than the average value of the bending modulus measured in the flow direction of the resin and the average value of the bending modulus measured in the direction perpendicular to the flow direction when a force is applied to the surface on the supporting layer side.

[0260] (use)

[0261] Examples of uses of the laminate of the present invention include various parts in industrial fields such as automobile parts and electrical and electronic equipment parts. In particular, since the laminate has high flame retardancy and excellent flame shielding properties, it can be preferably used in various housings and cases such as battery cases.

[0262] It is particularly preferably used as a battery case, and the battery is not particularly limited. For example, secondary batteries such as lithium ion batteries, nickel hydrogen batteries, lithium sulfur batteries, nickel cadmium batteries, nickel iron batteries, nickel zinc batteries, sodium sulfur batteries, lead storage batteries, and air batteries can be listed. Among them, lithium ion batteries are preferred, and are particularly suitable for suppressing thermal runaway of lithium ion batteries.

[0263] Furthermore, the present invention is useful for electric mobile equipment such as vehicles, ships, and transportation equipment such as airplanes that operate using electricity as energy, and the vehicles include hybrid vehicles in addition to electric vehicles (EVs).

[0264] A structure such as a battery case and a battery having a cell using the laminate of the present invention has high safety and is very useful for electric mobile devices using a battery module with an increased energy density in order to extend the driving distance.

[0265] [Battery case]

[0266] Hereinafter, a preferred embodiment (hereinafter sometimes referred to as a third embodiment) of a battery case as one of the above-mentioned uses will be described in detail.

[0267] Figure 7 The battery 100 includes a battery module 110 as an assembly of battery cells (battery cells), a battery pack 120 as an assembly of battery modules, and a battery case 130 for housing battery components such as the battery pack.

[0268] like Figure 1 As shown in the schematic diagram of the third embodiment, the battery case 130 of the third embodiment is formed by a laminate 10, which includes a resin layer 12 containing a flame retardant and a support layer 11 laminated on at least one surface of the resin layer. In addition, the resin layer 12 and the support layer 11 are arranged in order from the battery housing side, that is, the battery pack 120 side.

[0269] As described above, the resin layer 12 of the battery case of the third embodiment is located on the battery housing side, so when the battery module 110 catches fire, the resin layer 12 comes into contact with the flame. The mechanism of the battery case of the third embodiment to shield the flame is as described above in the resin composition section. It should be noted that the resin layer 12 in the battery case of the third embodiment has a flame retardant 13, preferably a fiber 14.

[0270] The battery pack of the third embodiment is composed of a laminate 10. Figure 1As shown in the schematic diagram of , the resin layer 12 is maintained by the support layer 11. Therefore, as described above, it is believed that when the resin layer 12 contacts the flame, the resin layer melts and falls, and the char formed by the flame retardant 13 contacting the flame is stably formed in the resin layer. When the resin layer and the support layer are arranged in sequence from the battery accommodating portion side, in the event of abnormal battery fire, the resin layer contacts the flame before the support layer. In this case, the resin layer perfectly functions as a heat insulating layer when contacting the flame, and can effectively protect the support layer from high heat. Therefore, by the heat insulating effect of the char, the temperature of the support layer will not rise to the softening point, so the support layer can exist stably and maintain the holding effect of the resin layer. As a result, it is believed that the flame will not penetrate for a long time. In particular, the laminate 10 as a preferred embodiment contains fibers 14 in the resin layer 12, so it can be considered that the flame retardant 13 is uniformly dispersed. Moreover, since the flame retardant is uniformly dispersed in the resin between the fibers, the char formed by the flame retardant contacting the flame is fixed in the gap between the fibers. Furthermore, the size of the coke formed by expansion when contacting the flame is limited by the gap between the fibers, thereby making the size of the coke formed uniform. It is believed that by combining the fixing effect of the fiber on the coke and the uniformization of the size of the coke, a dense coke is formed, and the flame shielding property of the laminate is significantly improved. In particular, it is believed that by making the ratio of the content of the dispersant to the flame retardant within a specific range, the flame retardant can be controlled to be uniformly present in the resin between the fibers, which can significantly improve the flame shielding property of the laminate.

[0271] As described above, the battery case of the third embodiment has a flame-blocking effect by arranging the resin layer and the support layer in this order from the battery housing portion side.

[0272] The fire-blocking mechanism of the battery case of the third embodiment is presumed as described above, and therefore, the battery case of the third embodiment preferably has the resin layer function as a flame-retardant heat-insulating layer when exposed to flame.

[0273] <Other options for laminated bodies>

[0274] As described above, in the laminate 10 constituting the battery case, the support layer may be located on one side of the resin layer, but it may also be located on the other side of the resin layer. Figure 3 As shown, the support layer 11 is provided on both sides of the resin layer 12. Since the support layer 11 is provided on both sides of the resin layer 12, the laminated body does not warp, which is preferable.

[0275] Moreover, if Figure 4As shown, the laminated body 10 constituting the battery case can also be a scheme in which two layers of resin layers 12 are present in a mode of sandwiching a support layer 11. In the case of this scheme, no matter which of the upper surface and the lower surface contacts the flame, it is a scheme that plays the effect of the present invention, and when making the battery case, there is no need to confirm the front and back of the laminated body. Example

[0276] Hereinafter, the present invention will be described in detail using Examples, but the present invention is not limited to these Examples.

[0277] (Evaluation method)

[0278] Evaluation of flame shielding properties (1)

[0279] For the laminates (injection test pieces) prepared in each of the examples and comparative examples, Figure 2 As shown, the flame of a burner at 1200° C. was exposed to the resin layer 12 side surface, and evaluation was performed to see whether the flame penetrated after 15 minutes. The evaluation criteria were as follows. As the injection test piece, the evaluation sample described below was used.

[0280] Evaluation Benchmarks

[0281] A: The flame does not penetrate.

[0282] B: Flame penetrates.

[0283] Evaluation of flame shielding properties (2)

[0284] For the laminates (injection test pieces) prepared in each of the examples and comparative examples, Figure 2 As shown, the surface on the resin layer 12 side was exposed to a flame of a burner at 1200° C., and the back surface temperature was measured after 15 minutes.

[0285] Evaluation of flame shielding properties (3)

[0286] The laminates (injection test pieces) prepared in the respective Examples and Comparative Examples were subjected to flame contact evaluation as follows. In addition, as the injection test pieces, evaluation samples described later were used.

[0287] (i)If Figure 8 As shown, the flame of a burner at 1200° C. was exposed to the resin layer 12 side surface, and evaluation was performed based on whether the flame penetrated after 15 minutes. The evaluation criteria were as follows.

[0288] (ii) If Figure 8 As shown, the surface of the support layer 11 was exposed to a flame of a burner at 1200° C., and evaluation was performed based on whether the flame penetrated after 15 minutes. The evaluation criteria were as follows.

[0289] Evaluation Benchmarks

[0290] A: The flame does not penetrate.

[0291] B: Flame penetrates.

[0292] Evaluation of flexural modulus and flexural strength

[0293] The laminates prepared in the examples and comparative examples were cut out in the flow direction (MD) and in the direction perpendicular to the flow direction (TD) using a circular saw, and the end faces were processed using a grinder to prepare test pieces in each direction (length × width × thickness: 40 mm × 25 mm × 2 mm). Hereinafter, the test pieces cut out in the MD direction are referred to as MD test pieces, and the test pieces cut out in the TD direction are referred to as TD test pieces. In the MD test piece, the flow direction of the test piece is the length direction, and in the TD test piece, the direction perpendicular to the flow direction is the length direction of the test piece.

[0294] The test pieces were measured for flexural modulus and flexural strength under the following conditions using a "2050 Universal Testing Machine" manufactured by INTSCO in accordance with JIS-K7171. Figure 6 The case of applying pressure from the A side of the resin layer (the side opposite to the nonwoven fabric, Figure 6 For these two cases, five measurements were performed respectively and the average values ​​were obtained.

[0295] (Measurement conditions)

[0296] Test environment: temperature 23±2℃, relative humidity 50%±10%.

[0297] (Measure the test piece after conditioning it in the same environment for more than 24 hours)

[0298] Test speed: 2mm / min

[0299] Distance between pivot points: 32mm

[0300] (1) Preparation of resin composition

[0301] As raw materials for the resin composition, the following raw materials were prepared.

[0302] (a) Polypropylene-based resin (component (A))

[0303] Made by Japan Polypropylene Co., Ltd., "NOVATEC (registered trademark) BC03B" (melt flow rate: 30 g / 10 minutes)

[0304] "NOVATEC (registered trademark) BC05B" manufactured by Japan Polypropylene Co., Ltd. (melt flow rate: 50 g / 10 minutes)

[0305] (b) Flame retardant (component (B))

[0306] Phosphorus-based flame retardant (Adek Corporation, ADK STAB FP-2500S, halogen-free intumescent flame retardant)

[0307] (c) Dispersant (component (D))

[0308] α-Olefin-maleic anhydride copolymer (manufactured by Mitsubishi Chemical Corporation, DIACANNA 30M, weight average molecular weight 7800)

[0309] (d) Antioxidants

[0310] (d-1) Phenolic antioxidant (manufactured by ADEKA Corporation, ADK STAB AO-60)

[0311] (d-2) Phosphite antioxidant (ADEKA STAB 2112, manufactured by ADEKA Corporation)

[0312] (e) Glass fiber reinforced thermoplastic resin (GF reinforced resin, (A) component + (C) component)

[0313] "Funcster (registered trademark)" manufactured by Japan Polypropylene Co., Ltd. (polypropylene resin / glass fiber = 50 / 50, pellet length 10 mm)

[0314] The above-mentioned (a) polypropylene resin, (b) flame retardant, (c) dispersant, (d) antioxidant and (e) GF reinforced resin were mixed in a manner such that each component had a ratio shown in the following Table 1 to prepare a resin composition. It should be noted that, although not described in Table 1, the ratio of the phenolic antioxidant (d-1) and the phosphite antioxidant (d-2) was 0.007 parts by mass relative to 100 parts by mass of the above-mentioned resin composition.

[0315] [Table 1]

[0316] Table 1

[0317]

[0318] (2) Raw materials of laminated body

[0319] As raw materials for the laminate, the following raw materials were prepared.

[0320] (f) Support layer

[0321] (f-1) Glass nonwoven fabric (manufactured by Oji F-Tex Co., Ltd., GMC-50G, weight per unit area 50 g / m 2 , thickness 0.36mm)

[0322] (f-2) Glass nonwoven fabric (manufactured by Oji F-Tex Co., Ltd., GMC-75G, weight per unit area 75 g / m 2 , thickness 0.53mm)

[0323] (f-3) Glass nonwoven fabric (manufactured by ORIBEST Co., Ltd., FAP-035, weight per unit area 35 g / m 2 , thickness 0.26mm)

[0324] (f-4) Aramid nonwoven fabric (manufactured by Oji F-Tex Co., Ltd., APT36, unit area weight 36 g / m 2 , thickness 0.50mm)

[0325] Examples 1 and 6

[0326] The resin composition obtained in the above (1) was laminated on the (f) support layer using an injection molding machine "FANUC ROBOSHOT α-S300iA" manufactured by FANUC Corporation to produce a sample for flame retardancy evaluation.

[0327] Specifically, a glass nonwoven fabric (f-1) was pre-arranged in a mold, and a resin composition having a formulation shown in Table 1 was injection molded thereon, thereby producing a test piece (1) having a length of 200 mm × a width of 200 mm × a thickness of 2.0 mm and a test piece (2) having a length of 200 mm × a width of 200 mm × a thickness of 3.5 mm. The final formulations are shown in Tables 2-1 and 2-2. It should be noted that the glass fibers in Tables 2-1 and 2-2 also include glass fibers derived from the supporting layer (f-1).

[0328] For example, the thickness of the resin layer of the evaluation sample (laminated body) obtained in Example 1 is 1.86 mm, and the thickness of the nonwoven fabric layer (support layer) is 0.14 mm. Therefore, the thickness of the resin layer is 13.3 times the thickness of the support layer. The thicknesses of the resin layer and the support layer of the evaluation samples in other examples are shown in Table 2-2. In addition, the flame shielding property of Example 1 was also evaluated (3). They are shown together.

[0329] The flame barrier properties were evaluated using the obtained evaluation samples, and the results are shown in Tables 2-1 and 2-2. In addition, the main molding conditions are as follows.

[0330] 1) Temperature conditions: barrel temperature (220°C), mold temperature (60°C)

[0331] 2) Injection conditions: injection pressure (200MPa), holding pressure (82MPa)

[0332] 3) Measuring conditions: screw speed (50rpm), back pressure (15MPa)

[0333] In addition, the flexural modulus and flexural strength were evaluated. The results are shown in Table 3.

[0334] Examples 2, 7 and 10

[0335] In Examples 2 and 7, evaluation samples were obtained in the same manner as in Examples 1 and 6, except that (f-2) was used instead of (f-1) in Examples 1 and 6, respectively. In Example 10, evaluation samples were obtained in the same manner as in Example 1, except that (f-2) was used instead of (f-1) to prepare a test piece (3) of 200 mm in length × 200 mm in width × 1.5 mm in thickness.

[0336] For example, the thickness of the resin layer of the evaluation sample (laminated body) obtained in Example 2 is 1.84 mm, and the thickness of the nonwoven fabric layer (support layer) is 0.16 mm. Therefore, the thickness of the resin layer is 11.5 times the thickness of the support layer. The thickness of the resin layer and the support layer of the evaluation samples in other embodiments are shown in Table 2-2. Using the obtained evaluation samples, flame shielding properties were evaluated, and the results are shown in Tables 2-1 and 2-2.

[0337] In addition, the flexural modulus and flexural strength were evaluated. The results are shown in Table 3.

[0338] Examples 3 and 8

[0339] In Examples 3 and 8, evaluation samples were obtained in the same manner as in Examples 1 and 6 except that two sheets of (f-2) were used instead of (f-1).

[0340] For example, the thickness of the resin layer of the evaluation sample (laminated body) obtained in Example 3 is 1.73 mm, and the thickness of the nonwoven fabric layer (support layer) is 0.27 mm. Therefore, the thickness of the resin layer is 6.4 times the thickness of the support layer. The thickness of the resin layer and the support layer of the evaluation samples in other embodiments are shown in Table 2-2. Using the obtained evaluation samples, flame shielding properties were evaluated, and the results are shown in Tables 2-1 and 2-2.

[0341] In addition, the flexural modulus and flexural strength were evaluated. The results are shown in Table 3.

[0342] Examples 4, 9, 11 and 12

[0343] In Examples 4 and 9, evaluation samples were obtained in the same manner as in Examples 1 and 6, except that (f-3) was used instead of (f-1) in Examples 1 and 6, respectively. In Example 11, evaluation samples were obtained in the same manner as in Example 1, except that (f-3) was used instead of (f-1) to prepare a test piece (3) of 200 mm long × 200 mm wide × 1.5 mm thick. In Example 12, evaluation samples were obtained in the same manner as in Example 1, except that (f-3) was used instead of (f-1) to prepare a test piece (4) of 200 mm long × 200 mm wide × 1.0 mm thick.

[0344] For example, the thickness of the resin layer of the evaluation sample (laminated body) obtained in Example 4 is 1.89 mm, and the thickness of the nonwoven fabric layer (support layer) is 0.11 mm. Therefore, the thickness of the resin layer is 17.2 times the thickness of the support layer. The thicknesses of the resin layer and the support layer of the evaluation samples in other embodiments are shown in Table 2-2. Using the obtained evaluation samples, flame shielding properties were evaluated, and the results are shown in Tables 2-1 and 2-2. In addition, flame shielding properties were also evaluated for Example 4 (3). Shown together.

[0345] In addition, the flexural modulus and flexural strength were evaluated. The results are shown in Table 3.

[0346] Example 5

[0347] Except that (f-4) was used instead of (f-1) in Example 1, an evaluation sample was obtained in the same manner as in Example 1. The thickness of the resin layer of the obtained evaluation sample (laminate) was 1.83 mm, and the thickness of the nonwoven fabric layer (support layer) was 0.17 mm. Therefore, the thickness of the resin layer was 10.8 times the thickness of the support layer. Using the obtained evaluation sample, a flame shielding evaluation was performed, and the results are shown in Table 2-1. In addition, a flame shielding evaluation (3) was also performed. Shown together.

[0348] In addition, the flexural modulus and flexural strength were evaluated. The results are shown in Table 3.

[0349] Comparative Example 1

[0350] A test piece was obtained in the same manner as in Example 1 except that the support layer (f) in Example 1 was not used. This test piece was a molded body consisting only of a resin layer. The flame barrier properties were evaluated in the same manner as in Example 1. The results are shown in Table 2-1.

[0351] In addition, the flexural modulus and flexural strength were evaluated. The results are shown in Table 3.

[0352] [Table 2]

[0353] Table 2-1

[0354]

[0355] [Table 3]

[0356] Table 2-2

[0357]

[0358] [Table 4]

[0359] Table 3

[0360]

[0361] The laminates of Examples 1 to 12 did not penetrate even when exposed to a 1200°C burner flame for 15 minutes, showing very good results. On the other hand, the molded body of Comparative Example 1 penetrated after about 90 seconds when exposed to a burner flame under the same conditions.

[0362] Furthermore, the flexural strength and flexural modulus of the laminated bodies of Examples 1 to 12 all showed good results.

[0363] As described above, one aspect of the present invention is described, but the present invention may also include the following aspects.

[0364] As other aspects of the present invention, the following aspects can be cited.

[0365] [1] A battery case comprising a resin layer containing a flame retardant and a support layer laminated on at least one surface of the resin layer, wherein the resin layer and the support layer are arranged in this order from the battery housing side.

[0366] [2] The battery case according to claim 1, wherein the resin layer is formed of a resin composition containing (A) a thermoplastic resin and (B) a flame retardant, and the supporting layer is a fiber layer formed of fibers (X).

[0367] [3] The battery case according to [2] above, wherein the fiber layer is a nonwoven fabric layer formed of a nonwoven fabric, a woven fabric layer formed of a woven fabric, or a knitted fabric layer formed of a woven fabric.

[0368] [4] The battery case according to [2] or [3] above, wherein the average fiber length of the fibers (X) constituting the fiber layer is 5 mm to 100 mm.

[0369] [5] The battery case according to any one of [2] to [4] above, wherein the resin composition further comprises (C) fibers having an average fiber length of 5 mm to 100 mm.

[0370] [6] The battery case according to any one of [2] to [5] above, wherein the resin composition further comprises (D) a dispersant.

[0371] [7] The battery case according to any one of [1] to [6] above, wherein the resin layer has a thickness of 0.5 mm to 50 mm.

[0372] [8] The battery case according to any one of [2] to [7] above, wherein the (B) flame retardant contains a phosphorus-based flame retardant.

[0373] [9] The battery case according to any one of [2] to [7] above, wherein the (B) flame retardant includes an intumescent flame retardant.

[0374]

[10] The battery case according to any one of [2] to [9] above, wherein the fibers (X) constituting the fiber layer include inorganic fibers.

[0375]

[11] The battery case according to

[10] above, wherein the inorganic fibers constituting the fiber layer include at least one selected from glass fibers, ceramic fibers, metal fibers, and metal oxide fibers.

[0376]

[12] The battery case according to any one of [5] to

[11] above, wherein the (C) fibers include inorganic fibers.

[0377]

[13] The battery case according to

[12] above, wherein the inorganic fiber includes at least one selected from glass fiber, ceramic fiber, metal fiber and metal oxide fiber.

[0378]

[14] The battery case according to [6] above, wherein the (D) dispersant comprises a copolymer of an α-olefin and an unsaturated carboxylic acid.

[0379]

[15] The battery case according to any one of [2] to

[14] above, wherein the (A) thermoplastic resin comprises a polypropylene resin, and the content of the polypropylene resin in the resin composition is 15% by mass to 80% by mass.

[0380]

[16] The battery case according to any one of [2] to

[15] above, wherein the content of the flame retardant (B) in the resin composition is 1% by mass to 40% by mass.

[0381]

[17] The battery case according to any one of [6] to

[16] above, wherein the content of the (D) dispersant is 0.1 to 20 parts by mass based on 100 parts by mass of the (B) flame retardant.

[0382] Furthermore, the following aspects can be listed as other aspects of the present invention.

[0383] [1] A laminate comprising a resin layer and a support layer laminated on at least one surface of the resin layer, wherein the resin layer is formed from a resin composition comprising (A) a thermoplastic resin and (B) a flame retardant, and satisfies at least one of the following conditions (a1) and (b1).

[0384] Condition (a1): The minimum value of the flexural modulus measured in accordance with JIS K7171 (ISO 178) is 1000 MPa or more.

[0385] Condition (b1): The minimum value of the flexural strength measured in accordance with JIS K7171 (ISO 178) is 10 MPa or more.

[0386] [2] The laminate according to [1] above, which satisfies the above condition (a1) and the following condition (a2).

[0387] Condition (a2): The minimum value of the flexural modulus measured in accordance with JIS K7171 (ISO 178) is 3000 MPa or more.

[0388] [3] The laminate according to [1] or [2] above, which satisfies the condition (a1) and the following condition (a3).

[0389] Condition (a3): The average value of the flexural modulus measured in the flow direction of the resin and the flexural modulus measured in a direction perpendicular to the flow direction, measured in accordance with JIS K7171 (ISO 178), is 3000 MPa or more.

[0390] [4] The laminate according to any one of [1] to [3] above, which satisfies the condition (b1) and the following condition (b2).

[0391] Condition (b2): The minimum value of the flexural strength measured in accordance with JIS K7171 (ISO 178) is 30 MPa or more.

[0392] [5] The laminate according to any one of [1] to [4] above, which satisfies the condition (b1) and the following condition (b3).

[0393] Condition (b3): ​​The average value of the bending strength measured in the flow direction of the resin and the bending strength measured in a direction perpendicular to the flow direction measured in accordance with JIS K7171 (ISO 178) is 30 MPa or more.

[0394] [6] The laminate according to any one of [1] to [5] above, wherein the support layer is a fiber layer formed of fibers (X).

[0395] [7] The laminate according to [6] above, wherein the fiber layer is a nonwoven fabric layer formed of a nonwoven fabric, a woven fabric layer formed of a woven fabric, or a knitted fabric layer formed of a knitted fabric.

[0396] [8] The laminate according to [6] or [7] above, wherein the average fiber length of the fibers (X) constituting the fiber layer is 5 mm to 100 mm.

[0397] [9] The laminate according to any one of [1] to [8] above, wherein the resin composition further comprises (C) fibers having an average fiber length of 0.05 mm to 100 mm.

[0398]

[10] The laminate according to any one of [1] to [9] above, wherein the resin composition further contains (D) a dispersant.

[0399]

[11] The laminate according to any one of [1] to

[10] above, wherein the thickness of the resin layer is 0.5 mm to 50 mm.

[0400]

[12] The laminate according to any one of [1] to

[11] above, wherein the flame retardant (B) comprises a phosphorus-based flame retardant.

[0401]

[13] The laminate according to any one of [1] to

[11] above, wherein the flame retardant (B) comprises an intumescent flame retardant.

[0402]

[14] The laminate according to any one of [6] to

[13] above, wherein the fibers (X) constituting the fiber layer include inorganic fibers.

[0403]

[15] The laminate according to

[14] above, wherein the inorganic fibers constituting the fiber layer include at least one selected from glass fibers, ceramic fibers, metal fibers, and metal oxide fibers.

[0404]

[16] The laminate according to any one of [9] to

[15] above, wherein the (C) fibers include inorganic fibers.

[0405]

[17] The laminate according to

[16] above, wherein the inorganic fiber includes at least one selected from glass fiber, ceramic fiber, metal fiber and metal oxide fiber.

[0406]

[18] The laminate according to

[10] above, wherein the (D) dispersant comprises a copolymer of an α-olefin and an unsaturated carboxylic acid.

[0407]

[19] The laminate according to any one of [1] to

[18] above, wherein the (A) thermoplastic resin comprises a polypropylene resin, and the content of the polypropylene resin in the resin composition is 15% by mass to 80% by mass.

[0408]

[20] The laminate according to any one of [1] to

[19] above, wherein the content of the flame retardant (B) in the resin composition is 1% by mass to 40% by mass.

[0409]

[21] The laminate according to any one of

[10] to

[20] above, wherein the content of the (D) dispersant is 0.1 to 20 parts by mass based on 100 parts by mass of the (B) flame retardant.

[0410]

[22] A method for manufacturing a laminate, which is a method for manufacturing a laminate as described in any one of [1] to

[21] above, comprising a step of impregnating a support with a resin composition to form a support layer laminated on at least one surface of the resin layer, wherein the thickness of the support before impregnation with the resin composition is 0.01 mm to 30 mm.

[0411]

[23] The method for producing a laminate according to

[22] above, wherein the compression rate of the support body defined as the ratio of the thickness of the support layer in the laminate body to the thickness of the support body before impregnation with the resin composition is 15% to 75%.

[0412] Industrial Applicability

[0413] The laminate of the present invention has extremely excellent flame barrier properties and is therefore useful as a material for various industrial parts requiring high safety, such as aircraft, ships, automobile parts, electrical and electronic equipment parts, and building materials. In particular, it can be applied to various housings and shells of batteries that have conventionally used metals, which contributes to the safety of automobiles, and it can be expected that the energy efficiency will be improved and CO2 emissions will be reduced due to lightweighting.

Claims

1. A laminate comprising a resin layer and a support layer laminated on at least one surface of the resin layer, The resin layer is formed of a resin composition comprising (A) a thermoplastic resin, (B) a flame retardant, and (C) fibers. The thickness of the laminate is 0.5 mm or more, The thickness of the resin layer is at least twice the thickness of the support layer.

2. The laminate according to claim 1, wherein The supporting layer is a fiber layer formed of fibers (X).

3. The laminate according to claim 2, wherein: The fiber layer is a nonwoven fabric layer formed of nonwoven fabric, a woven fabric layer formed of woven fabric, or a knitted fabric layer formed of knitted fabric.

4. The laminate according to claim 2 or 3, wherein: The average fiber length of the fibers (X) constituting the fiber layer is 5 mm to 100 mm.

5. The laminate according to claim 1, wherein The average fiber length of the fibers is 0.05 mm to 100 mm.

6. The laminate according to claim 1, wherein The resin composition further includes (D) a dispersant.

7. The laminate according to claim 1, wherein The thickness of the resin layer is 0.5 mm to 50 mm.

8. The laminate according to claim 1, wherein The (B) flame retardant includes a phosphorus-based flame retardant.

9. The laminate according to claim 1, wherein The (B) flame retardant includes an intumescent flame retardant.

10. The laminate according to claim 2 or 3, wherein The fibers (X) constituting the fiber layer include inorganic fibers.

11. The laminate according to claim 10, wherein The inorganic fibers constituting the fiber layer include at least one selected from glass fibers, ceramic fibers, metal fibers, and metal oxide fibers.

12. The laminate according to claim 1, wherein The (C) fibers include inorganic fibers.

13. The laminate according to claim 12, wherein The inorganic fiber includes at least one selected from glass fiber, ceramic fiber, metal fiber and metal oxide fiber.

14. The laminate according to claim 6, wherein The (D) dispersant includes a copolymer of an α-olefin and an unsaturated carboxylic acid.

15. The laminate according to claim 1, wherein The (A) thermoplastic resin includes a polypropylene resin, and the content of the polypropylene resin in the resin composition is 15% by mass to 80% by mass.

16. The laminate according to claim 1, wherein The content of the flame retardant (B) in the resin composition is 1% by mass to 40% by mass.

17. The laminate according to claim 6, wherein The content of the (D) dispersant is 0.1 to 25 parts by mass based on 100 parts by mass of the (B) flame retardant.

18. A method for producing a laminate, which is a method for producing the laminate according to claim 1, wherein: The method comprises the step of impregnating a support with a resin composition to form a support layer laminated on at least one surface of the resin layer, wherein the thickness of the support before impregnation with the resin composition is 0.01 mm to 30 mm.

19. The method for producing a laminate according to claim 18, wherein: The support body compression rate defined as the ratio of the thickness of the support layer in the laminate to the thickness of the support body before impregnation with the resin composition is 15% to 75%.

Citation Information

Patent Citations

  • PREPARATION METHOD OF PROPYLENE / ETHYLENE-alpha-OLEFIN BLOCK COPOLYMER

    JP2008189893A

  • Glass filament-containing flame-retardant resin composition and molded article

    JP2011088970A

  • Flame-retardant polyolefin resin composition

    JP2013119575A

  • Battery case for vehicle

    JP2014062189A

  • Compression molded flame retardant and high impact strength ultra high molecular weight polyethylene composition

    US5286576A